1992
DOI: 10.1038/355836a0
|View full text |Cite
|
Sign up to set email alerts
|

Defective anion transport activity of the abnormal band 3 in hereditary ovalocytic red blood cells

Abstract: Hereditary ovalocytosis is common in some areas of Melanesia and South East Asia where malaria is endemic. These red cells resist invasion by malarial parasites in vitro and ovalocytic individuals are less parasitized than normal. This has been attributed to the greater rigidity of ovalocytic red cells. It has been suggested that South East Asian ovalocytosis results from the heterozygous presence of an altered membrane anion transporter (band 3). We have used the polymerase chain reaction to clone the abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
121
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(131 citation statements)
references
References 17 publications
8
121
1
Order By: Relevance
“…cDNAs and Mutagenesis-cDNAs encoding human kAE1 (27,34), human eAE1 SAO (Southeast Asian Ovalocytosis) (11,35), and mouse eAE1 E699Q (36) were previously described. cDNAs encoding human CA2 (gift of W. Sly, St. Louis University, St. Louis, MO) and the CA2 mutants V143Y (37) (gift of C. Fierke, University of Michigan, Ann Arbor, MI) and ⌬ N 17/C206S cDNA (38) (gift of U. Carlsson, University of Linkoping, Linkoping, Sweden) were subcloned into the oocyte expression vector pXT7.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…cDNAs and Mutagenesis-cDNAs encoding human kAE1 (27,34), human eAE1 SAO (Southeast Asian Ovalocytosis) (11,35), and mouse eAE1 E699Q (36) were previously described. cDNAs encoding human CA2 (gift of W. Sly, St. Louis University, St. Louis, MO) and the CA2 mutants V143Y (37) (gift of C. Fierke, University of Michigan, Ann Arbor, MI) and ⌬ N 17/C206S cDNA (38) (gift of U. Carlsson, University of Linkoping, Linkoping, Sweden) were subcloned into the oocyte expression vector pXT7.…”
Section: Methodsmentioning
confidence: 99%
“…The heterozygous hAE1 mutant SAO (AE1 ⌬400 -408) is associated with Southeast Asian ovalocytosis, and contributes to dRTA as a compound heterozygous mutation (10). AE1 SAO transports neither sulfate in erythrocytes (35) nor Cl Ϫ in oocytes (42,43). The engineered mAE1 mutant E699Q cannot mediate Cl Ϫ /Cl Ϫ exchange, despite its enhanced exchange of extracellular sulfate for either intracellular sulfate or Cl Ϫ (36).…”
Section: Functional Effects Of Sequential Truncation Of the Kae1 C-mentioning
confidence: 99%
“…It is experimentally clarified that the biophysical consequences of this mutation are a marked decrease in lateral mobility of band 3 in the membrane, and an increase in membrane extensional rigidity (Mohandas et al, 1992). And it is also shown that the protein having nine amino acids deletion is defective in anion transport activity (Schofield et al, 1992a).…”
mentioning
confidence: 99%
“…All transport measurements were performed within the linear range of the assay. The [ 35 S]sulfate influx into red cells was measured using variant and control cells at 10% hematocrit, and the number of DIDS-binding sites was determined by titration of sulfate transport as described previously (25). The V max and apparent K m for [ 35 S]sulfate influx were calculated from sulfate influx measurements in the absence of DIDS using sulfate concentrations between 0.4 and 50 mM.…”
Section: Methodsmentioning
confidence: 99%